Assessment of awareness about rabies and the animal bite among the staff nurses in a medical institute in Lucknow - Chopra, Deepak; Jauhari, Nidhi; Dhungana, Homnath; ., Nasrah (International Journal Of Community Medicine And Public Health, 2017)
Background: People have very basic knowledge about rabies and its prevention. Health workers are usually the first ones to come in contact with a victim of animal bite. Research Question- “What is the awareness and practices about rabies and animal bite in the Health workers/paramedical staff?” Objectives of the study were 1) assessment of the awareness of staff Nurses about rabies and animal bite management; 2) to study the practices of staff nurses after an animal bite and 3) to find association of socio-demographic factors with the knowledge level. Methods: Observational cross sectional conducted at Integral Hospital, IIMSR among 256 staff nurses (response rate 95%) between January 2017 to February 2017. Purposive Convenience Sampling method was used. Data recording by interview on a questionnaire. A scoring pattern was described. Results: The current study observed that the knowledge and awareness of the study subjects on the rabies/ animal bite was variable, high in some aspects and low/poor in others. Majority of the subjects had poor grading of knowledge. Sex, marital status and religion were statistically significantly associated with the kowledge gradient. Conclusions: There is a need for generating awareness about rabies and animal bite. Recommendations: There is a need for sensitization of health workers so that their knowledge can be enhanced and can be translated into proper practices.